TAREKAT SYADZILIYAH DAN PENGARUH IDEOLOGI ASWAJA DI INDONESIA - Nasrullah, Muhammad (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2020)
Tarekat is one of the real forms of Sufism. This sect is more of a pattern of daily practical life than a philosophical conceptual pattern. If one of the goals of Sufism is to reach Allah SWT alone in the sense of enlightenment, then tarekat is a method, method or path that needs to be taken to achieve the goal of Sufism. The teachings of the tarekat also developed in several countries, including Indonesia. Tarekat of Syadziliyah, is one of the Sunni sects practiced by Muslims in Indonesia. Tarekat of Shadziliyah sect emphasizes its teachings on the inner attributes of the spiritual path of the sect. The teachings of the Syadziliyahâ€™s tarekat were greatly influenced by Al-Ghazali's Sufi thought. This Syadziliyah sect emphasizes on those whose names are happy (Al-Farh), willing (Al-Ridha), and always grateful (Al-Syukr) for the blessings of Allah SWT. This order can be very applied and wisdom can be taken. That is, in this tarekat there is no deviation at all or misguidance in its application.Â